Effect of nanosilica on the thermal, mechanical, and dielectric properties of polyarylene ether nitriles terminated with phthalonitrile. Issue 2 (25th September 2013) - Tong, Lifen; Pu, Zejun; Chen, Zhiran; Huang, Xu; Liu, Xiaobo
<x xml:space="preserve">Abstract</x> Nanosilica/polyarylene ether nitriles terminated with phthalonitrile (SiO2/PEN‐t‐Ph) composites were prepared by hot‐press approach. To ensure the nano‐SiO2 can disperse uniformly, the solution casting method combined with ultrasonic dispersion technology had been taken previously. The mass fraction of nano‐SiO2 particles was varied to investigate their effect on the thermal, mechanical, and dielectric properties of the nanocomposites. From scanning electron microscope images, it was found that the nanoSiO2 particles were dispersed uniformly in the PEN‐t‐Ph matrix when the addition of nano‐SiO2 was less than 16.0 wt%. However, when the mass fraction of nano‐SiO2 increased to 20.0 wt%, the nano‐SiO2 particles tend to self‐aggregate and form microns sized particles. Thermal studies revealed that nano‐SiO2 particles did not weaken the thermal stabilities of the PEN‐t‐Ph matrix. Mechanical investigation manifested that the SiO2/PEN‐t‐Ph nanocomposites with 12.0 wt% nano‐SiO2 loading showed the best mechanical performance with tensile strength of 108.2 MPa and tensile modulus of 2107.5 Mpa, increasing by 14% and 19%, respectively as compared with the pure PEN‐t‐Ph film. Dielectric measurement showed that the dielectric constant increased from 3.70 to 4.15 when the nano‐SiO2 particles varied from 0.0 to 20.0 wt% at 1 kHz. Therefore, such composite was a good candidate for high performance materials at elevated temperature environment. POLYM. COMPOS., 35:344–350, 2014. © 2013 Society of Plastics Engineers